A high-throughput colorimetric assay for glucose detection based on glucose oxidase-catalyzed enlargement of gold nanoparticles. Issue 38 (11th September 2015) - Xiong, Yanmei; Zhang, Yuyan; Rong, Pengfei; Yang, Jie; Wang, Wei; Liu, Dingbin
Abstract : A simple high-throughput colorimetric assay for detecting glucose in clinical samples based on glucose oxidase-catalyzed enlargement of gold nanoparticles. Abstract : We developed a simple high-throughput colorimetric assay to detect glucose based on the glucose oxidase (GOx)-catalysed enlargement of gold nanoparticles (AuNPs). Compared with the currently available glucose kit method, the AuNP-based assay provides higher clinical sensitivity at lower cost, indicating its great potential to be a powerful tool for clinical screening of glucose.